Cebuano and Maranao marriage a contrastive analysis - De los Santos, Lucia P. 1916- (s.n.], 1973)
This study is an attempt toward creating a measure of understanding of our Muslim brothers in the two Lanao Provinces- the Maranaos. The study is limited to the subject of marriage, as this is one in which apparently Maranao practices differ markedly from those of the Christian Filipinos. The basis of comparison is Cebuano marriage. Maranao marriage practices are compared to Cebuano marriage practices: the target culture is Maranao; the native culture is Cebuano.